Genetic Improvement of Teak (Tectona grandis) in Forest Research Institute : an overview - Sharma, S. L.; Rawat, M. S. (Indian Forester, 1998)
Teak was taken as a priority species for genetic improvement since the inception of Genetics Section. a Branch and now a Division. in FRI. Since then a lot of work has been done in the different aspects of this species and salient features of tbe same have been given in chronological order.